2017
DOI: 10.1108/jedt-04-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Duration estimation model for bridge construction projects in Ghana

Abstract: Purpose A major concern for construction professionals at the rural road agency in Ghana is the problem of fixing contract duration for bridge construction projects in rural areas. The purpose of the study was to develop a tool for construction professionals to forecast duration for bridge projects. Design/methodology/approach In all, 100 questionnaires were distributed to professionals at the Department of Feeder Roads to ascertain their views on the work items in a bill of quantities (BOQ) that impact sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…Several studies have attempted to model the relationship between highway projects features and their durations in early stages (Nevett et al, 2021, Titirla and Aretoulis 2019, Son et al, 2019, Okere, 2019, Nani et al, 2017, Pesko et al, 2017. Pesko et al, (2017) concluded that integrating the estimation of duration and cost can compromise the significance of input data, leading to reduction of estimating accuracy compared to that based on separate estimation.…”
Section: Cost and Duration Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have attempted to model the relationship between highway projects features and their durations in early stages (Nevett et al, 2021, Titirla and Aretoulis 2019, Son et al, 2019, Okere, 2019, Nani et al, 2017, Pesko et al, 2017. Pesko et al, (2017) concluded that integrating the estimation of duration and cost can compromise the significance of input data, leading to reduction of estimating accuracy compared to that based on separate estimation.…”
Section: Cost and Duration Estimationmentioning
confidence: 99%
“…However, no recent study is comprehensive and combines project characteristics (Sharma et al, 2021, Meharie and Shaik, 2020, Son et al, 2019, project scope (Qiao et al, 2019, Okere, 2019, Juszczyk, 2020, cost and schedule information (Sharma et al, 2021, Titirla andAretoulis, 2019), level of technical complexity (Karaca et al, 2020, Gardner et al, 2017 and expected risk profile for different project types in one robust general model with acceptable accuracy. Some studies even use item quantities for duration and/or cost prediction in the conceptual phase when they may not be precisely determined (Nevett et al 2021;Pesko et al 2017;Nani et al 2017). Besides, some studies rely solely on datasets that comprise factors whose probability and/or impact are determined subjectively by experts in questionnaires (Le et al, 2021).…”
Section: Cost and Duration Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Google scholar search engine was used to check the universal database about the issues. [23] used multi factors that could be adopted to forecast road duration at the early stage of the project. This study adopted the available factors after preparing the bill of quantity by the estimator and pricing the whole road activities.…”
Section: 1identification Of Factorsmentioning
confidence: 99%
“…Moreover, the accuracy of the decision-making relies heavily on the outcomes of a reliable bridge condition forecasting model ( [2,15]; Lu and Zheng 2017). Many recent researches focus on improving model forecasting accuracy and shed some light on improving forecasting accuracy [2,4,[12][13][14][15]. However, many of the researches ignore the forecasting reliability and provide incomplete picture regarding forecasting accuracy.…”
Section: Introductionmentioning
confidence: 99%